Cultural Values and Architectural Developments of the Acehnese Traditional House Museum in 2020-2022 - Fahrizal, Fahrizal; Muslem, Muslem (Riwayat: Educational Journal of History and Humanities, 2023)
Each region has its own customs and culture, such as in Aceh, a part of the culture is the Acehnese traditional house. Acehnese houses are houses that are shaped like a stage, this research aims to find out how the cultural and architectural values of the Acehnese traditional house museum are are in the Meureudu city park and how it is developing. Data collection techniques in this study are direct observation, interviews and documentation, while the approach is descriptive qualitative. The results of this study are that the Aceh House Museum is a luxury house made from teak, merbau, and semantok wood which is supported by 28 pillars and decorated with seven kinds of carved ornaments and in each porch there are historical relics and other cultural values. This Aceh house museum was established in 2020, but will only be visited by tourists at the end of 2021 and 2022.